FAKTOR-FAKTOR YANG MEMPENGARUHI STRESS TERHADAP LANJUT USIA DI POSYANDU LANSIA PUSKESMAS BROMO TAHUN 2017 - PEBRINA WANTI SARAGIH (LP2MTBM MAKARIOZ, 2018)
Aging process (aging) is a natural process that is accompanied by a decrease in physical condition with the visible decline in organ function. This situation tends to potentially cause health problems in general and mental health so spur the emergence of stress specifically in the elderly. This study aims To determine the factors that affect stress on elderly in Posyandu Elderly Bromo Puskesmas Year 2017. The type of research is analytic that is to know the factors - factors that affect stress of elderly in Posyandu Elderly Bromo Puskesmas Year 2017, and the sample in this study is the entire population of elderly in Posyandu Elderly Bromo Puskesmas as many as 30 elderly people using total sampling method. Data collecting was done on June 13, 2017, by using questionnaires and data processing method using SPPSS (Statistical Product and Service Solution) program version 14.0. The results showed that the problem groups causing stress in the elderly were psychological problems as much as 25 respondents or 83.3%, economic problems as much as 23 respondents or 76.7%, socio-cultural issues as much as 19 respondents or 63.3%, and health problems 18 respondents or 60%. The result of chi-square test shows that p (0,007) <0,05 there is influence of economic problem with stress of elderly, p (0,007) <0,05, meaning there is influence between socio-cultural problem with stress elderly, p (0,024) <0, 05, meaning there is influence between health problems with stress elderly, p (0,014) <0,05, meaning there is significant influence between psychological problem with stress of elderly. From the results of the study can be concluded that from 30 elderly people who experience the stress of elderly there are several factors that influence the economic problems, socio-cultural issues, health problems, and psychological problems. It is expected that medical personnel should improve the quality of health service for the elderly and for the students to dig more knowledge about factors that influence stress to the elderly, to be able to apply it in health service duty.